L’école est finie ! L’ère trans-moderne du savoir-relation et la fin de la transmission ? - Béatrice Mabilon Bonfils (Éducation et Socialisation)
Beyond the joke, the institutions flicker, to the test of the plural and the trans-modernity. The modes of youthful socialization are becoming more complex, and school audiences are changing. Knowledge is overturned: its construction, epistemology, modes of diffusion, modes of access ... especially in the digital age. Knowledge becomes relationship. Yet, beyond the rhetoric, the school form remains traditional, transmissive, vertical. Inclusion/exclusion processes take over from supervisory/control processes and translate into a shaky identity in the work of the teachers, a firming of the forms of control and adaptive ruses, a sort of survival strategy of a school in mutations. The loss of intelligibility of scholastic knowledge is obvious. The diagnosis is based on several empirical investigations concerning the identity at work of teachers, adaptive ruses of pupils, numerical practices of adolescents, high school representations of the role of the school, school suffering.